2022
DOI: 10.3390/su14169968
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Labor, Rapport, and Word of Mouth in Fitness Organizations

Abstract: The fitness service industry requires employees to interact with members, placing great importance on their emotional expression to manage service quality and the subsequent organizational outcomes. Emotional labor may be a significant psychologically related factor that plays a critical role in building pleasant interactions between a fitness organization’s employees and its members. Thus, grounded in the emotional contagion theory, this study examines the predictability of perceived emotional labor strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…Image and reputation were highlighted compared to the other dimensions and had a higher coefficient value. Another study showed that rapport was positively associated with word of mouth in the fitness industry [ 39 ]. Hence, these dimensions are of particular importance when providing a higher quality of service.…”
Section: Discussionmentioning
confidence: 99%
“…Image and reputation were highlighted compared to the other dimensions and had a higher coefficient value. Another study showed that rapport was positively associated with word of mouth in the fitness industry [ 39 ]. Hence, these dimensions are of particular importance when providing a higher quality of service.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that a large number of the sample's fitness businesses have not yet developed an established code of conduct that can be communicated to their customers through the companies' key individuals, employees, and overall business practices, linking the businesses' ethical image to their customers' responses [101,102]. In general, health and fitness businesses are facing employment and labor policy issues due to temporary personnel, and it is proposed that the intangible, heterogeneous, and inseparable nature of their services leads customers to largely determine the success of the service during their interactions with the brands' employees [103,104].…”
Section: Discussionmentioning
confidence: 99%
“…As part of their job responsibilities, service employees are expected to engage in emotional labor, a term referring to the intentional effort to express specific emotions required by the organization while suppressing others, during their direct interactions with customers [ 12 ]. Many studies have shown that emotional labor is significantly associated with the individual well-being of employees, including job satisfaction and job burnout (please see a meta-analysis of Hulsheger and Schewe [ 13 ]), as well as with organizational outcomes, such as perceived service quality and customer satisfaction [ 14 , 15 ] in various job settings, including tourism [ 16 ], the fitness industry [ 17 ], and education [ 18 ], and among athletic coaches [ 19 ], professors [ 20 ], and government employees [ 21 ]. The significance of emotional labor in service sectors is well recognized [ 22 ], but research on its connection to participant sports is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Participant sports involve unique features of service provision, and service providers must make conscious efforts to develop positive employee-customer interfaces to ensure a pleasurable experience for the customer [11]. Therefore, it is crucial to explore the function of emotional labor in these customer-employee interactions [17].…”
Section: Introductionmentioning
confidence: 99%